ANALISIS PENGARUH FAKTOR PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI - Mahmudatul Himma (Politeknik Negeri Malang, 2018)
The purpose of this research is 1) Knowing and analyzing the influence of Career development on employee performance simultaneously 2) Knowing and analyzing the influence of Career development on employee performance partially at PT Asuransi Jiwa Syariah Bumiputera (AJSB) Malang . The number of sample there are 44 respondents at agent employees in PT AJSB Malang. The sampling technic in this research was total sampling. The tools analysis used multiple regression analysis. The results of the study show that career development variables consist of Variables Influence of justice in careers, Attention to supervision, Awareness about opportunities, Interest of workers, Career satisfaction, simultaneously have a significant influence on employee performance. partially , Attention to supervision, opportunity awareness, interest in workers, have a significant influence, while the influence of fairness in careers, and career satisfaction does not show significant value